Volume 4: Advanced Manufacturing Processes; Biomedical Engineering; Multiscale Mechanics of Biological Tissues; Sciences, Engin 2012
DOI: 10.1115/esda2012-82108
|View full text |Cite
|
Sign up to set email alerts
|

Laser Sintering Process Analysis: Application to Chromium-Cobalt Alloys for Dental Prosthesis Production

Abstract: Rapid prototyping is an effective way to build prototypes. This process, now called AM (Additive Manufacturing), is suited to realize functional single part or for small batch production. Evolution of AM is now in the way of serial production. In the field of medical applications and more precisely dentistry, AM is a way of increasing numbers of elements produced compared to classic production by lost wax casting. To increase production quality, it is necessary to have a high monitoring and control of process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Cobalt-chrome has been studied by various groups for dental applications. Faure et al 146 recorded results of 7000 dental elements produced over a span of 6 months. Averyanova et al 147 studied the fabrication of 99% dense Co-Cr dental crown and bridges over a period of 14 months and concluded that SLM has good repeatability and these parts made by SLM meet the traditions standards.…”
Section: Other Metalsmentioning
confidence: 99%
“…Cobalt-chrome has been studied by various groups for dental applications. Faure et al 146 recorded results of 7000 dental elements produced over a span of 6 months. Averyanova et al 147 studied the fabrication of 99% dense Co-Cr dental crown and bridges over a period of 14 months and concluded that SLM has good repeatability and these parts made by SLM meet the traditions standards.…”
Section: Other Metalsmentioning
confidence: 99%
“…Given that the criterion applied in the aeronautics industry for Advances in Materials Science and Engineering RD is greater than 99%, these values could be considered to be exceptional for the manufacturing process [27]. For most applications, such a high RD is not required and a correlated reduction in mechanical strength is traded for speed and economic fabrication [28][29][30]. However, for dental metallic devices, the RD is also relevant to accomplish a tissue-friendly, void-free satin finish, which is achieved via electrolytic polishing to prevent fitting and cleaning problems on the fitting surface of denture frameworks.…”
Section: Microstructural Analysismentioning
confidence: 99%
“…Given that the high quality criterion applied in the aeronautics industry is RD greater than 99%, these values could be considered to be exceptional for the manufacturing process [27]. For most applications, such a high RD is not required and a correlated reduction in mechanical strength is traded for speed and economic fabrication [28][29][30]. However, for dental metallic devices, the RD is also relevant to accomplish a tissue-friendly, void-free, satin finish, which is achieved via electrolytic polishing to prevent fitting, and cleaning problems on the fitting surface of denture frameworks.…”
Section: Relative Densitymentioning
confidence: 99%